Incentive and Signaling Effects of Bonus Payments: An Experiment in a Company - Marvin Deversi; Lisa Spantig (Center for Economic Studies and ifo Institute (CESifo), 2023)
Economists and management scholars have argued that the scope of incentives to increase cooperation in organizations is limited as their use signals the prevalence of free-riding among employees. This paper tests this hypothesis experimentally, using a sample of managers and employees from a large company. We exogenously vary whether managers are informed about prevailing cooperation levels among employees before they can set incentives to promote cooperation. In addition, employees matched to informed managers learn that the manager could base their incentive choice on cooperation levels. We find no evidence for the hypothesized signaling effect. Having an informed manager set the incentive does not change employees' be-liefs about the cooperativeness of others. Incentives hence have strong positive effects on cooperative beliefs, irrespective of information. The absence of the signaling effect seems related to the perception of managers' intentions, a mitigating but understudied factor.
Keywords: C91; D83; D91; D01; 330; cooperation; incentives; signalling; crowding out; experiment